2016
DOI: 10.1002/elan.201501102
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Parathion Degrading Enzyme‐based Nano‐hybrid Biosensor for Enhanced Methyl Parathion Recognition

Abstract: Enzyme‐based electrochemical biosensors with sufficient sensing specificity are useful analytical tools for detection of biologically important substances in complicated systems. Here, we present the design of a nano‐hybrid biosensor for the specific and sensitive detection of methyl parathion (MP). The nano‐hybrid sensing film was prepared via the formation of Au nanoparticals (AuNPs) on silica nanoparticles (SiNPs), mixing with multiwall carbon nanotube (MWNTs) and subsequent immobilization of methyl parathi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Silica based NPs are chemical inert, bio-compatible and optical transparent, and can maintain cell viability (Ye et al, 2016). Immobilization of microbial cells on SiNPs could be a way to produce a stable functional biohybrid material.…”
Section: Othersmentioning
confidence: 99%
“…Silica based NPs are chemical inert, bio-compatible and optical transparent, and can maintain cell viability (Ye et al, 2016). Immobilization of microbial cells on SiNPs could be a way to produce a stable functional biohybrid material.…”
Section: Othersmentioning
confidence: 99%
“…Among various nanoparticles, silica nanoparticles have shown their superiority due to their characteristic features like biocompatibility, wide availability, ease of functionalization, high chemical, and mechanical stability, and high surface area [19][20][21]. Ponamoreva et al [22] have synthesized a stable functional biohybrid material by integrating yeast cells with silica for biosensor application.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first report on the use of this hybrid material to develop thirdgeneration biosensors. So far, only a nanohybrid biosensor based on MWCNTs, AuNPs and silica nanoparticles, developed for the detection of methyl parathion (Ye et al, 2016), and a nanocomposite material of single-walled carbon nanotubes (SWCNTs) and gold-mesoporous silica Janus nanoparticles developed for the bienzymatic glucose biosensing (through the use of glucose oxidase (GOx), horseradish peroxidase (HRP) and hydroquinone as redox mediator) have been developed (Boujakhrout et al, 2015). The use of MWCNTs coated with mesoporous silica as signal tag for the electrochemical aptasensing of thrombin (Zhang et al, 2013) and mucin 1 (Chen et al, 2014) has been aso reported.…”
Section: Introductionmentioning
confidence: 99%